Analysis of Validity and Reliability of the Health Literacy Index for Female Marriage Immigrants (HLI-FMI). (May 2016) - Yang, Sook Ja; Chee, Yeon Kyung; An, Jisook; Park, Min Hee; Jung, Sunok
The purpose of this study was to obtain an independent evaluation of the factor structure of the 12-item Health Literacy Index for Female Marriage Immigrants (HLI-FMI), the first measure for assessing health literacy for FMIs in Korea. Participants were 250 Asian women who migrated from China, Vietnam, and the Philippines to marry. The HLI-FMI was originally developed and administered in Korean, and other questionnaires were translated into participants' native languages. The HLI-FMI consisted of 2 factors: (1) Access-Understand Health Literacy (7 items) and (2) Appraise-Apply Health Literacy (5 items); Cronbach's α = .73. Confirmatory factor analysis indicated adequate fit for the 2-factor model. HLI-FMI scores were positively associated with time since immigration and Korean proficiency. Based on classical test theory and item response theory, strong support was provided for item discrimination and item difficulty. Findings suggested that the HLI-FMI is an easily administered, reliable, and valid scale.